The regulatory framework of trade finance: from BASEL I to BASEL III - BAICU, Claudia (Annals of Spiru Haret University. Economic Series, 2011)
The global crisis revealed several weaknesses in the international framework of banking regulation. Consequently, the Basel Committee on Banking Supervision (BCBS) proposed a package of measures to strengthen the resilience of the banking sector. Besides the positive effects they have on financial stability, the new regulatory provisions affect the ability of banks to provide trade finance. Therefore, the banking industry considers that regulators have not taken into account the low-risk profile of activity. Starting from this premise, the paper consists of three parts. In the first part, the role and objectives of the BCBS are presented; the second part is designed to review the most important trade instruments and to underline the tendencies in trade finance; finally, the last part highlights the regulation of trade finance under the Basel I, Basel II and Basel III regimes, and some unintended consequences of the Basel III framework.